Selection processes for school principals in Latin America: Brazil, Chile, Colombia and Peru - Felipe Aravena (Arizona State University, 2020)
School leadership is key for improving teaching practices and student learning outcomes. Thus, the selection process for school principals is important for school improvement. This article presents a comparative case study describing four national contexts, Brazil/Rio de Janeiro (democratic model), Chile (politicized model), Colombia (managerial model) and Peru (mixed model). The study reports that principal´s selection systems in Latin-American region are diverse in terms of their scope, the agencies involved in the process, who makes the final decision, and the use of selection strategies. Finally, it concludes with proposals for improvement selection processes of school principals in Latin America.